Accumulation mechanism of natural gas hydrate in the Qilian Mountain permafrost, Qinghai, China - Zhang, Fugui; Yang, Zhibin; Zhou, Yalong; Zhang, Shunyao; Yu, Linsong (Frontiers in Energy Research, 2022)
Qilian Mountain is the only permafrost area in China where natural gas hydrate have been obtained through scientific drillings. Many studies have been done on natural gas hydrate in permafrost regions from the perspectives of sedimentology and petroleum geochemistry, especially on reservoir forming conditions and exploration methods. However, there are still more divergences in its evolutionary process, time and accumulation mechanism. In this study, a total of 500 core samples were collected in the gas hydrate drilling wells DK-8, DK13-11, and DK12-13 in the Qilian Mountain permafrost. Gas components, carbon isotopes of methane, total organic carbon (TOC), chloroform bitumen "A", the concentrations of kerogen element, and vitrinite reflectance (Ro) are analyzed. The results show that the hydrocarbon source rocks in the Middle Jurassic Muli formation and the Upper Triassic Galedesi formation are good source rocks, with good total organic carbon content and chloroform bitumen "A". The rocks of Muli formation rocks are at the mature stage of organic matters, the organic matter types are mainly Ⅱ1 and Ⅱ2, and the peak of generating crude oil with immense petroleum-associated gas. And the rocks of Galedesi formation are in highly mature stage, producing more gas, and offering efficient gas for the natural gas hydrate, the organic matter types are mainly Ⅲ and Ⅱ1. Laboratory experiments and numerical analysis indicate that the formation of natural gas hydrate in the Qilian Mountain has experienced three phases: the gas migration and aggregation in Late Jurassic to Early Cretaceous, the overall uplift in Middle and Late Miocene to Pliocene, and the free gas to natural gas hydrate deposits in Quaternary. The experimental results show that the gas sources, permafrost thickness and structural conditions played a key role in controlling the occurrence and distribution of gas hydrate.